PERFORMANCE OF PADDY CUM- PRAWN CULTURE IN RAINFED LOW LAND ECOSYSTEM OF SUNDERBANS - MAITI, D.; CHAKRABORTY, P. B. (Journal of Indian Fisheries Association, 2015)
Performance of both paddy (Var. NC 492) and prawn Penaeus monodon) were assessed for two years during wet-season in rainfed lowland ecosystem with a view to study the economic viability of paddycum- prawn culture in the coastal saline zone of West Bengal. Both mono and dual culture of paddy and prawn were tried in the study. Fingerlings of prawn(@ 35,000 ha-1) of 10-15 mm size were reared for about three and half months with and without fish feed. It was observed that addition offish feed resulted in higher (57.7%) production of prawn (2.65 mgha-1) but not rice. Such increase in prawn productiQn was 1.6 times higher when no feed was provided and 1.4 times higher when grown as sole crop. However, paddy, whether grown as mono or mixed culture, did not differ in yield significantly. In dual culture, the benefit m cost ratio was higher (6.83) when prawn was grown with feed and it was maximum (36.0) when grown without feed as sole crop. The study, therefore, indicates that paddy-cum-prawn culture under low land ecosystemÂ· of the coastal saline zone is enterprising particularly for small and marginal farmers who fear to take risk of growing prawn alone at the cost of paddy.